2015
DOI: 10.1016/j.ijid.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of Tuberculosis in Denmark 1998-2010. Cost analysis in patients and their spouses

Abstract: We estimate the direct costs per TB patient to be €10,509. TB patients and their households are characterized by increasingly lower employment income, lower employment rate, and higher dependency on public transfer, but the socio/economic deterioration is rather a risk factor for TB than a direct consequence of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…TB patients and their households are characterized by increasingly lower employment income, lower employment rate and higher dependency on public transfer, but the socio/economic deterioration is rather a risk factor for TB [22]. In this study 48% were moderate monthly income, other results found in Denmark 53% [23], in Sudan 14.9% [24], this is due to the difference in the standard of living between countries and most of limited income families as well as unemployment and lack of opportunities for work (Figure 1). Figure 1 Relationship among socio-demographical characteristics variables and overall knowledge assessments.…”
Section: Discussionmentioning
confidence: 39%
“…TB patients and their households are characterized by increasingly lower employment income, lower employment rate and higher dependency on public transfer, but the socio/economic deterioration is rather a risk factor for TB [22]. In this study 48% were moderate monthly income, other results found in Denmark 53% [23], in Sudan 14.9% [24], this is due to the difference in the standard of living between countries and most of limited income families as well as unemployment and lack of opportunities for work (Figure 1). Figure 1 Relationship among socio-demographical characteristics variables and overall knowledge assessments.…”
Section: Discussionmentioning
confidence: 39%
“…Surprisingly, since 2012 only a few studies on the costs of non-MDR-TB have been performed in other European countries, and even less information has been provided in those on the single components of aggregated costs: DE VRIES et al [16], in their complete country-wide review analysis which included 1138 patients with non-MDR-TB and 20 with MDR/XDR-TB, estimated the per-patient treatment costs of non-MDR-TB at €7850, but did not address indirect costs or other cost components. FLOE et al [17] calculated the excess health-related costs of Danish TB patients and their spouses between 1998 and 2010 by matching 8433 patients with 337 070 controls and 3485 spouses with 17 403 controls, but did not include costs related to contact investigation procedures. Finally, GULLÓN et al [18], in their prospective study on 312 patients in Spain collected between September 2014 and September 2015, estimated the average cost per TB case at €10 262.62 but also included MDR-TB cases and assumed that the 2012 figure of €921.80 provided by DIEL et al [2] as an estimate for the per-patient cost of contact tracing would also apply to Spain, without performing their own calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The mean cost of managing TB in Russia over 12 months was about US$ 572 per cases (Atun et al, 2006). Meanwhile, the cost in Denmark is higher with direct cost per TB patient was about €10.509 (Fløe et al, 2015). High costs are also borne by immigrant patients in the Netherlands.…”
Section: The Economic Impact Of Tuberculosismentioning
confidence: 99%